1. The problem statement, all variables and given/known data 2. What is wrong with the following "proof"? Let x = y. Then x2 =xy, x2 - y2 =xy - y , (x + y)(x -y) = y(x - y), x + y = y, 2y = y, 2= 1. 2. Relevant equations It's obvious that x + y =/= y, but I do not know how to "prove" this, i.e. which proof from algebra is applicable here. My hunch is that it is the Distributive Property? 3. The attempt at a solution I honestly am not sure where to start with this. All I can see is that dividing (x-y) out from step 3 to step 4 is what causes the inequality.